Persistent current induced by vacuum fluctuations in a quantum ring - Kibis, O. V. (2014)
We study theoretically interaction between electrons in a quantum ring embedded in a microcavity and vacuum fluctuations of electromagnetic field in the cavity. It is shown that the vacuum fluctuations can split electron states of the ring with opposite angular momenta. As a consequence, the ground state of the electron system in the quantum ring can be associated with nonzero electric current. Since a ground-state current flows without dissipation, such a quantum ring gets a magnetic moment and can be treated as an artificial spin.